Penerapan Fatwa DSN-MUI No. 17 Tentang Sanksi Atas Nasabah Mampu Yang Menunda-Nunda Pembayaran: Studi Kasus Pada BMT Al Fath - Deni Nuryadin (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2021)
This research is a qualitative research that uses descriptive analytical methods to the implementation of the Fatwa National Sharia Council No. 17 On the Sanctions for Capable Customers for Delaying Installment Payments on Murabahah Products to BMT AL FATH Pamulang. BMT Al Fath is also known as BMT Al Fath IKMI which was founded in 1996. BMT Al Fath has customers who are micro entrepreneurs, around the Ciputat market. One of the financing products is murabahah financing. During the last 5 years, the highest murabahah financing was 26% with a total of Rp. 21,529,716,342, - of the total murabahah financing was Rp. 97,049,706,660, -. BMT Al Fath, Pamulang provided a warning letter for customers who were negligent, but did not apply a fine for customers who were negligent in the installment scheme. Because it is feared that the implementation of this scheme will cause usury which will actually harm various parties.Keywords : Fatwa DSN-MUI, Penalty, and Murabahah Financing.